Law Enforcement Efforts for Child Murder - Wahyu Latief (Estudiante Law Journal, 2023)
The purpose of this study was to find out what are the factors that cause children to commit murder crimes, as well as to find out what efforts are made by the Gorontalo City Police in overcoming the occurrence of a murder crime committed by children. This research was conducted using empirical legal research methods. The results of this study can be seen that the factors that cause children to commit murder are internal factors which include unstable emotional factors, misunderstanding factors, vengeful factors, psychological factors, and weak faith factors. While on external factors, namely family factors, economic factors, alcoholic beverage factors, and child neglect factors. While the countermeasures carried out by the Gorontalo City Police are pre-emptive efforts which are basic actions in the form of appeals, then preventive efforts are continued efforts preemptive in the form of direct and repressive preventive measures which are punitive efforts or law enforcement efforts